The Level of Hard Competencies and the Amount of Earnings – Evaluation by Selected Nonparametric Methods - Grześkowiak, Alicja (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article discusses the comparison of earnings achieved in groups of people who declare different levels of following hard competences: information analysis abilities, computer skills, machine operation, making calculations and foreign language skills. The analysis is based on data from the nationwide study of the Human Capital in Poland. Nonparametric statistical methods are used to evaluate the differences in earnings: the kernel estimation and the concept of relative distributions. The results show that better skills are associated with higher earnings and that there are differences depending on the type of competencies.